Synergistic effect of ZnO and TiO2 nanoparticles on the thermal stability and mechanical properties of glass fiber‐reinforced LY556 epoxy composites. Issue 9 (30th June 2021) - Thipperudrappa, Sridhar; Hiremath, Anupama; Kurki Nagaraj, Bharath
Abstract: The article discusses the fabrication, mechanical characterization, and heat resistance of nano ZnO‐TiO2 ‐filled glass fiber‐reinforced LY556 epoxy composites, with focus on the synergistic effect of ZnO and TiO2 nanofillers. The fabrication of the composite laminates is achieved by the addition of the nanofillers in different wt% ranging from 1 to 5 wt%. The composites are prepared using simple hand layup technique followed by curing under vacuum. The 3D atomic force microscopy scans indicated even distribution of the nanofillers up to 2 wt% loading. Severe agglomeration of the nanofillers is evident for 3 to 5 wt% loading. The surface roughness, microhardness, flexural strength, tensile strength, and impact strength of the composites indicate a relationship with dispersion, wt% loading, and the wettability of the nanofiller with the LY556. In general, it is found that the incorporation of hard nanofillers favored the improvement of impact strength to a greater extent compared to tensile and flexural strengths. Detailed analysis of the obtained mechanical property values favors an optimum 2 wt% incorporation of the selected nanofillers to obtain improvement in various strength values of the fabricated composites. The thermal stability of the fabricated composites improved through the incorporation of ceramic nanofillers. Abstract : Fabrication of nanofiller‐filled glass fiber‐reinforced epoxy composites.